Risk weighting, private lending and macroeconomic dynamics - Michael Donadelli; Marcus Jüppner; Lorenzo Prosperi (Deutsche Bundesbank, 2019)
According to current regulation, European banks can apply zero risk weights to sovereign exposures in their balance sheet, irrespective of the assigned rating. We show that a zero risk weighting of sovereign bonds has implications by distorting banks' asset allocation decisions. Due to the lower regulatory cost of sovereign bonds, banks invest more in those bonds at the expense of lending to the real sector. To quantify the effect of this distortion, we build a standard RBC model featuring financial intermediation and a government sector calibrated to the euro area economy. Financial regulation is introduced via a penalty function that punishes banks if they deviate from the target capital ratio. We study the zero risk weight policy during normal times when there is no sovereign default risk and find that a policy introducing positive risk weights on government bonds has both long-run effects and stabilising properties with respect to the business cycle. This policy makes the steady state lending spread on loans to firms decline, stimulating investment and output. Also, it stabilises the lending spread, leading to a lower volatility of investment and output.
Keywords: E44; E32; G21; G32; 330; sovereign bonds; risk weighting; RBC; lending